Thermophilic aerobic digestion using aquaculture sludge from rainbow trout aquaculture facilities: effect of salinity - Chun, Jihyun; Kim, Su Min; Ko, Gwangil; Shin, Hyo Jeong; Kim, Minjae; Cho, Hyun Uk (Frontiers in Microbiology, 2024)
The objectives of this study were to evaluate the potential of using thermophilic aerobic digestion (TAD) to hydrolyze aquaculture sludge, and to investigate the hydrolysis efficiency and changes in microbial community structure during TAD at 0, 15, and 30 practical salinity units (psu). As digestion progressed, soluble organic matter concentrations in all reactors increased to their maximum values at 6 h. The hydrolysis efficiency at 6 h decreased as salinity increased: 2.42% at 0 psu, 1.78% at 15 psu, and 1.04% at 30 psu. The microbial community compositions at the genus level prominently differed in the relative abundances of dominant bacteria between 0 psu and 30 psu. The relative abundance of genera Iodidimonas and Tepidiphilus increased significantly as salinity increased. Increase in the salinity at which thermophilic aerobic digestion of aquaculture sludge was conducted altered the microbial community structure, which in turn decreased the efficiency of organic matter hydrolysis.